CGIAR capacity sharing with NARS to use digital sequence information in conservation and crop improvement programs. A submission from CGIAR for consideration by the Governing Body of the International Treaty - Lopez Noriega, Isabel; Rouard, Mathieu; Halewood, Michael; Hamilton, Ruaraidh Sackville (2025)
CGIAR submitted this report in response to the Plant Treaty Secretary's open request to Contracting Parties and stakeholders for information regarding their efforts ‘to reduce the existing gap on capacity between developed and developing countries’ regarding the use of digital sequence information/genomic sequence information (DSI/GSD).